CNA pulsations associated with Pc 3-5 magnetic pulsations - Higuchi, Yoshihiro; Shibuya, Senkichi; Sato, Natsuo (1986)
P(論文) The correlation between Pc 3-5 magnetic pulsations and fluctuations of cosmic noise absorption (i. e., CNA pulsation) observed at Syowa Station in Antarctica is examined. It is confirmed that the coherency of the D component of Pc 3-4 magnetic pulsations to CNA pulsations is much higher than that of the H component of Pc 3-4 magnetic pulsations. On the other hand, the H component of Pc 5 magnetic pulsations tends to be more correlated with CNA pulsations rather than the D component of Pc 5 magnetic pulsations. The relative amplitude of magnetic pulsations against that of CNA pulsations depends on pulsation frequency. These characteristics suggest some differences in generation and modulation mechanisms of CNA pulsations for PC 3-5 magnetic pulsations. The polarization of Pc 3-5 magnetic pulsations associated with CNA pulsations is predominantly counterclockwise independent of pulsation period during the morning hours. departmental bulletin paper